Maize II - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Shupikai Ndigwirei, a Zimbabwean agriculture student explains cultural and mechanical methods of weed control for maize crops.